Catalytic effect of Mn2+, Fe3+ and Mg2+ ions on desulfurization using phosphate rock slurry as absorbent - Nie, Yunxiang; Li, Shuai; Dai, Jinfeng; He, Dedong; Mei, Yi (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •The promotion effect of Mn2+, Fe3+ and Mg2+ on SO2 removal is revealed.•Trace Mn2+ and Fe3+ ions can enhance about 19%–31.5% SO2 adsorption capacity.•74.1% of activation energy is reduced when Mn2+ and Fe3+ are used to catalyze S(IV).•A radical chain reaction mechanism of S(IV) catalyzed by Mn2+/Fe3+ is proposed.•The Mn2+/Fe3+ promote the formation of SO3− radicals in the chain-initiating step. Wet phosphate rock flue gas desulfurization is a new and promising technology, which has drawn increasing attention in recent years. The effect of Mn2+, Fe3+ and Mg2+ dissolved from phosphate rock on removal efficiency of SO2 were systematically investigated in this paper. The XRD, FT-IR, SEM, XPS, IC and ICP were used to characterize the reacted products, demonstrating that these metal ions have promotive effect on the purification of SO2. Especially, trace Mn2+ and Fe3+ ions can rose up about 19%–31.5% SO2 absorption capacity compared to the system without metal ions. Furthermore, the catalytic effect of these metal ions on the oxidation of S(IV) were compared, by adding them to the sodium bisulfite aqueous solution system. The order of catalytic capability of metal ions to S(IV) is: Mn2+ > Fe3+ > Mg2+. Interestingly, in the simultaneous presence of Mn2+ and Fe3+, the catalytic synergism between them toward S(IV) oxidation is exhibited. And only 16.56 kJ/mol of activation energy is needed, which is reduced by 74.1% compared to systems without catalyst. Consequently, a satisfactory result for absorption of SO2 can be obtained although the concentrations of Mn2+ and Fe3+ in phosphate rock slurry is low. Additionally, the catalytic mechanism of Mn2+ and Fe3+ towards S(IV) was investigated by reaction barrier and free energy calculation.